The analysis of student’s mathematical communication ability viewed from learning styles through project based learning models on cylinder and cone materials - Fitriana, Rodliyatul Wulan; Isnarto, Isnarto; Prabowo, Ardhi (Unnes Journal of Mathematics Education, 2018)
The aims of this study were to know student’s mathematical communication ability reach minimum criteria of mastery learning, know teacher’s and student’s activity, and describe student’s mathematical communication ability viewed from learning styles. The learning methode used in this study was mix mehod. The population were ninth grader of students from MTsS Hidayatul Athfal Pekalongan and obtained the sample was class IX D as research class. The methods which have been used to collect data were documentation, questionaire, observation, test, and interview. The result in this study show that (1) student’s mathematical communication with Project Based Learning models reach minimum criteria of mastery learning, (2) teacher’s activity on Project Based Learning from first meeting tol fourth meeting was in very good category, (3) student’s activity on Project Based Learning from first meeting tol fourth meeting was in very good category, (4) subject with visual, auditory, and kinesthetic learning styles on the top category were able to fulfill entire mathematical communication indikators. Subject with visual learning styles on the middle category was able to fulfill two indikators. Subject with auditorial and kinesthetic learning styles on the middle category were able to fulfill three indikators. While subject with visual, auditory, and kinesthetic learning styles on the bottom category were able to fulfill just one indikator.